Cross-Country and Cross-Sector Analysis of Transparency of Monetary and Financial Policies. (IMF Working Papers; Working Paper ;, 2003)
In this paper we construct indices of transparency of monetary and financial policies, based on self-evaluations carried out by 135 IMF member countries in 1999, and use them to identify transparency patterns across different policies and country groups. We find that across all countries, transparency is highest in the formulation and conduct of monetary policy and lowest in insurance supervision and deposit-insurance oversight. Across country groups having similar political/economic characteristics, the average degree of transparency is highest in advanced countries and lowest in developing ones for both monetary policy and those financial policies for which there are differences between country group means.